Characterising activity and diet compositions for dementia prevention: protocol for the ACTIVate prospective longitudinal cohort study. Issue 1 (5th January 2022) - Smith, Ashleigh E; Wade, Alexandra T; Olds, Timothy; Dumuid, Dorothea; Breakspear, Michael J; Laver, Kate; Goldsworthy, Mitchell R; Ridding, Michael C; Fabiani, Monica; Dorrian, Jillian; Hunter, Montana; Paton, Bryan; et al.
Abstract : Introduction: Approximately 40% of late-life dementia may be prevented by addressing modifiable risk factors, including physical activity and diet. Yet, it is currently unknown how multiple lifestyle factors interact to influence cognition. The ACTIVate Study aims to (1) explore associations between 24-hour time-use and diet compositions with changes in cognition and brain function; and (2) identify duration of time-use behaviours and the dietary compositions to optimise cognition and brain function. Methods and analysis: This 3-year prospective longitudinal cohort study will recruit 448 adults aged 60–70 years across Adelaide and Newcastle, Australia. Time-use data will be collected through wrist-worn activity monitors and the Multimedia Activity Recall for Children and Adults. Dietary intake will be assessed using the Australian Eating Survey food frequency questionnaire. The primary outcome will be cognitive function, assessed using the Addenbrooke's Cognitive Examination-III. Secondary outcomes include structural and functional brain measures using MRI, cerebral arterial pulse measured with diffuse optical tomography, neuroplasticity using simultaneous transcranial magnetic stimulation and electroencephalography, and electrophysiological markers of cognitive control using event-related potential and time frequency analyses. Compositional data analysis, testing for interactions between time point and compositions, will assess longitudinal associations between dependent (cognition, brain function) and independent (time-use and diet compositions) variables. Conclusions: The ACTIVate Study will be the first to examine associations between time-use and diet compositions, cognition and brain function. Our findings will inform new avenues for multidomain interventions that may more effectively account for the co-dependence between activity and diet behaviours for dementia prevention. Ethics and dissemination: Ethics approval has been obtained from the University of South Australia's Human Research Ethics committee (202639). Findings will be disseminated through peer-reviewed manuscripts, conference presentations, targeted media releases and community engagement events. Trial registration number: Australia New Zealand Clinical Trials Registry (ACTRN12619001659190).